2023 cyberbiosecurity summit underscores challenges associated with cybersecurity and the rapidly growing bioeconomy - Nicholas Guise; David Pattie; Kenneth B. Yeh; Kemper Talley; Rachel Fennell Fezzie (Taylor & Francis Group, 2024)
The 2 November 2023 Cyberbiosecurity Summit at Georgia Tech Research Institute's (GTRI) headquarters in Atlanta united cybersecurity and biotechnology stakeholders to address safeguarding of bio-based industries. Goals included identifying cyberbiosecurity vulnerabilities and establishing prevention best practices for emerging biotech hardware, software, data and bio-based systems. The Summit highlighted risks and explored mitigation strategies for a safer bioeconomy. Key takeaways include: (1) as genome databases proliferate globally, it becomes more likely that these databases will become targets for cyberbiosecurity attacks; (2) the biotech community should not view cybersecurity as an impediment to research, but rather as a national security and global health imperative for proactive investment and workforce training; (3) the bioeconomy depends on a vulnerable supply chain for software; and (4) mapping of a biological attack surface, inspired by traditional cybersecurity assessments, would facilitate identification of vulnerabilities of cyber-bio-physical systems and the development of protective measures for the bioeconomy.